(untitled) (Bangladesh Medical Journal, 2022)
In-hospital mortality and morbidities are significantly higher in patients who undergo coronary artery bypass graft (CABG) surgery having a depressed left ventricular function or a left main (LM) coronary artery disease. Due to the improvement in technique and clinical outcome, Off-pump Coronary Artery Bypass (OPCAB) is thought to be beneficial in patients with depressed left ventricular function by avoiding prolonged ischemic time. This study was performed with an aim to assess whether OPCAB is better than conventional on-pump CABG (CCAB) in these sub-groups of patients. We purposively selected 100 patients with left main coronary artery disease (defined as ≥50% stenosis) with reduced left ventricular ejection fraction (defined as ejection fraction 40% or less) who underwent elective CABG in National Institute of Cardiovascular Diseases (NICVD) between January 2014 and December 2020. Among them OPCAB was done in 50 patients and conventional CABG in another 50 patients. Both groups had similar pre-operative parameters. Total operative time, intubation time, blood loss, requirement for blood and blood products, intensive care unit (ICU) stay and hospital stay were all significantly lower in the OPCAB group. Post-operative complications were not statistically different among the two groups. Study finds that patients with left main coronary artery disease with left ventricular dysfunction can be safely revascularized in OPCAB technique. Bangladesh Med J. 2021 Sept; 50(3): 14-19